La escuela: un horizonte posible para prevenir las violencias hacia las mujeres - Castro Soto, Niyireth (Universidad de San Buenaventura - Cali, 2017)
Legislative progress on the issue of gender equality in Colombia are not enough now for the reduction of violence exerted on women, as they continue to record high rates of violence. It is necessary to review aspects and dimensions associated with the phenomenon; so, as education comes to play an important role as a scenario of responsibility in the construction and transformation of men and women in our society. Student relations, content and mediated practices are identified by sexist cultural stereotypes that reproduce patterns of naturalized violence and normalized against women, being a supportive and forced to rebuild new social dynamics that change patterns of teaching and sexist relations scenario for the new models. This research is configured from the interest in the role of the school as a setting for the prevention of violence against women, from theoretical approaches, which argue the need for revision of curriculum content, sexist language and teacher training from the perspective of gender. Enabling a process in which the school is achieved converted into a training space for Gender Equality to prevent violence as a contribution to human development.